Comparative Review of Long-Term Energy Storage Technologies for Renewable Energy Systems - Andrijanovits, A.; Hoimoja, H.; Vinnikov, D. (Elektronika ir Elektrotechnika, 2012)
Sustainability of electric power systems will involve very large use of renewable energy sources for power production. Wind power is one of the cleanest and safest of all the renewable methods of generating electricity. However, wind power fluctuations have adverse impacts on power quality, such as local voltage and system frequency. Energy storage devices will be needed at different locations in the power system, to store the surplus of power from renewable sources for later use during non-generation time periods or low power generation time periods. This paper will give an overview of different storage technologies. Ill. 10, bibl. 20, tabl. 3 (in English; abstracts in English and Lithuanian). DOI: http://dx.doi.org/10.5755/j01.eee.118.2.1168